Teacher Written Feedback on English as a Foreign Language Learners’ Writing: Examining Native and Nonnative English-Speaking Teachers’ Practices in Feedback Provision - Cheng, Xiaolong; Zhang, Lawrence Jun (Frontiers in Psychology, 2021)
While previous studies have examined front-line teachers’ written feedback practices in second language (L2) writing classrooms, such studies tend to not take teachers’ language and sociocultural backgrounds into consideration, which may mediate their performance in written feedback provision. Therefore, much remains to be known about how L2 writing teachers with different first languages (L1) enact written feedback. To fill this gap, we designed a study to explore native English-speaking (NES) and non-native English-speaking (NNES) (i.e., Chinese L1) teachers’ written feedback practices in the Chinese tertiary context. Our study collected 80 English as a foreign language (EFL) students’ writing samples with teacher written feedback and analyzed them from three aspects: Feedback scope, feedback focus, and feedback strategy. The findings of our study revealed that the two groups of teachers shared similar practices regarding feedback scope and feedback strategies. Both NES and NNES EFL teachers used a comprehensive approach to feedback provision and they delivered their feedback directly and indirectly. However, their practices differed greatly with regard to feedback focus. Specifically, when responding to EFL students’ writing, NES teachers showed more concern with global issues (i.e., content and organization), whereas NNES teachers paid more attention to linguistic errors. With a surge in the recruitment of expatriate NES and local NNES English teachers in China and other EFL countries, our study is expected to make a contribution to a better understanding of the two groups of EFL teachers’ pedagogical practices in written feedback provision and generate important implications for their feedback provision.